MCMV-infected maize attracts its insect vector Frankliniella occidentalis by inducing β-myrcene - Huang, Weiling; Wei, Shujun; Zhou, Tao; Fan, Zaifeng; Cao, Lijun; Li, Zhihong; Guo, Shaokun (Frontiers in Plant Science, 2024)
Maize lethal necrosis is attributed to the accumulation of maize chlorotic mottle virus (MCMV), an invasive virus transmitted by insect vectors. The western flower thrips (WFT) can shift host to maize, thus promoting the spread of MCMV. However, our understanding of the characteristics and interactions involved in the transmission of MCMV is still limited. This study finds that non-viruliferous WFTs showed a 57.56% higher preference for MCMV-infected maize plants compared to healthy maize plants, while viruliferous WFTs showed a 53.70% higher preference for healthy maize plants compared to MCMV-infected maize plants. We also show for the first time that both adults and larvae of WFT could successfully acquire MCMV after 1 min of acquisition access period (AAP) and after 48 h of AAP, WFT could transmit MCMV in an inoculation access period of 1 h without a latent period. Both adults and larvae of WFT can transmit MCMV for up to 2 days. Furthermore, the decreasing number of viruliferous WFTs and transmission rates as time progressed, together with the transcriptomic evidence, collectively suggest that WFTs transmit MCMV in a semipersistent method, a mode of transmission requiring minutes to several hours for acquisition access and having a retention time of several hours to a few days. Additionally, β-myrcene can attract WFTs significantly and is detected in Nicotiana benthamiana plants transiently expressing MCMV CP (coat protein), which is consistent with results in MCMV-infected maize plants through the metabolomic profiling and the preference analyses of WFT. Therefore, this study demonstrates the indirect interaction between MCMV and WFT by inducing maize to synthesize βmyrcene to attract insect vectors. The exploration of specific interactions between MCMV and WFT could help to expand the mechanism studies of virus-vector-host plant interaction and put forward a new insight for the combined control of MCMV and WFT through the manipulation of plant volatiles and key insect genes.